1985
DOI: 10.1121/1.2022304
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in auditory temporal processing

Abstract: Age-related changes in auditory temporal processing were investigated using a two-tone flutter-fusion paradigm. Ten elderly and ten young subjects (mean age 71.3 and 22.2 years, respectively) listened to pure-tone pairs at six discrete interstimulus intervals (ISIs). The duration of the second tone (T2) was held constant at 100 ms. The duration of the first tone (T1) was variable. Subjects were instructed to adjust the duration of T1 at each ISI until they perceived flutter or fusion. In both groups, when crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Within the framework of the model, it has been shown that this outcome could be the result of a reduced rate of processing that affects excitation, inhibition, and decay of activation. In a sense, this across-the-board reduction in processing rate encompasses all three of the hypotheses concerning age differences that were mentioned earlier: reduced efficiency in inhibition (Hasher et al, 1991), a deficit in the rate of priming (MacKay & Burke, 1990), and reduced rate of decay of activation (Robin & Royer, 1989; Kline & Schieber, 1982). For example, the present data are consistent with the hypothesis that older adults are less efficient in inhibiting the processing of irrelevant stimuli (Hasher et al, 1991), in this case, the primes.…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…Within the framework of the model, it has been shown that this outcome could be the result of a reduced rate of processing that affects excitation, inhibition, and decay of activation. In a sense, this across-the-board reduction in processing rate encompasses all three of the hypotheses concerning age differences that were mentioned earlier: reduced efficiency in inhibition (Hasher et al, 1991), a deficit in the rate of priming (MacKay & Burke, 1990), and reduced rate of decay of activation (Robin & Royer, 1989; Kline & Schieber, 1982). For example, the present data are consistent with the hypothesis that older adults are less efficient in inhibiting the processing of irrelevant stimuli (Hasher et al, 1991), in this case, the primes.…”
Section: Methodsmentioning
confidence: 75%
“…These three processing parameters that drive the network model may be useful in understanding the age effects in primed picture naming. In fact, something akin to each of these processes has been cited by one theorist or another as a possible source of performance deficits in older adults: MacKay and Burke (1990) suggested a deficit in the rate of priming (analogous to excitation in the present model); Hasher, Stoltzfus, Zacks, and Rypma (1991) proposed reduced inhibitory effectiveness; and reduced rate of decay of activation for older adults has been demonstrated at the perceptual level as increased stimulus persistence (e.g., Robin & Royer, 1989; Kline & Schieber, 1982). In a series of simulations, the effect of altering each of the parameters of the network model was explored to determine which could best account for the data for older adults in Experiment 1, that is, the longer response times associated with aging along with a pattern of semantic facilitation and inhibition effects over time that did not differ from that of the young subjects.…”
Section: Methodsmentioning
confidence: 86%
“…Age-related phenomena compatible with increases in sensory persistence have been found in both auditory (Raz et al, 1989; Robin & Royer, 1989) and visual (Kline & Schieber, 1985; Royer & Gilmore, 1985) domains. A potential neural mechanism of increased stimulus persistence has been proposed by Robin and Royer, who suggested that there is an age-related increase in inhibitory interactions of cells sensitive to onset and offset of the stimuli.…”
Section: Discussionmentioning
confidence: 95%
“…Thus far, a number of experimental data have indicated that subjective time varies depending on our TIP ability. Evidence for this has come from experiments having to do with age-related changes in the perception of temporal order 29 , gap detection 30,31,32,33 , duration discrimination 34,35,36,37 , temporal bisection 38,39 , and time estimation 40,41,42,43 . For example, Philips et al 44 found that in general, elderly people (aged approx.…”
Section: Introductionmentioning
confidence: 99%